The Development of the Kurdish issue in Iraq and its impact on Iraqi-Iranian relations 1962-1966. Historical Study (Journal of the College of Basic Education, 2026)
The Kurdish issue in Iraq has had a significant impact on Iraqi-Iranian relations, which share common interests in land, water, and ethnicity. The Kurdish issue has been a source of instability between the two countries.Therefore, the importance of the research lies in the great change that occurred in the Iraqi-Irish relations when the Shah of Iran adopted the support of the Kurdish nationalist movement with money and weapons against the Iraqi government and used it as a pressure card on Iraq, not for the sake of the victory of the Kurds, but rather to occupy the Iraqi governments and weaken them so that Iran could achieve its interests in Iraq.The research is divided into two chapters and a number of topics. The first chapter deals with Iraqi-Iranian relations during the royal era, and the cooperation between the two countries to suppress the Kurdish uprisings, especially the uprising of 1943-1945. It also includes the merits of the revolution of July 14, 1958, and the Shah of Iran’s fear of the republican regime in Iraq and its impact on the Iranian people.Especially after the constitutional recognition that the Kurds obtained in Iraq after the revolution of July 14, 1958, and the return of the leader of the Kurdistan Democratic Party, Mulla Mustafa Barzani, to Iraq, who enjoyed great esteem and influence among the Kurds of Iran.While the second chapter highlighted the Iranian government's exploitation of the tension that arose between the leadership of the Kurdish movement and the Iraqi government from 1961-1966, the Kurds received significant military and logistical support despite the Iraqi government's demands that Iran stop its support and close its borders to prevent Kurdish fighters. The Kurds used it as Iraq demanded that it not interfere in Iraqi affairs until the Kurds were able to achieve a military victory in the Battle of Mount Handrin Which had a great impact on the military and civilian establishment in Iraq, and Iraqi-Iranian relations.